KARAKTERISTIK MORFOLOGI RUMPUT GAJAH DAN RAJA DI TANAH VULKANIK DENGAN PEMBERIAN BAHAN ORGANIK - A. Hanifa; Y.B.P. Subagyo; Lutojo Lutojo (BUANA SAINS, 2012)
The experiment was aimed to investigate the effect of grasses variety and organic matter on the morphology characteristic of Elephant and King grasses in Volcanic soil of Klakah village, Selo sub district, Boyolali regency. A completely randomized design in a series of 2 x 4 experiment, with 4 replications were used to arrange the experiment. The first factor consisted of two grasses variety: Elephant grass (R1) and King grass (R2). The second factors were kinds of organics matter: D0 (no organic matter); D1 (organic matter 5 ton/ha); D2 (organic matter 10 t/ha) and D3 (organic matter 15 t/ha). The results showed highly significant effect of dietary organic matter on the morphological characteristic of tiller total of Elephant and King grasses. Both treatments showed significant interaction (P=0.05) on tiller total. Dietary organic matter factor did not affect plant height of two kind of grasses, but significantly affected leaf and culm ratio. The kinds of grasses factor showed highly significant effect (P=0.01) on plant height, but significant effect on leaf and culm ratio. The organic matter increased number of tiller total on two kinds of grasses. King grass responded better than elephant grass on height plant and leaf and culm ratio. It is concluded that dietary organic matter at 5 t/ha could be recommended to be applied on volcanic soil